Effect of oral salbutamol and slow-release aminophylline on exercise tolerance in chronic bronchitis. Issue 10 (October 1981) - Leitch, A G; Morgan, A; Ellis, D A; Bell, G; Haslett, C; McHardy, G J
Abstract : In a double-blind placebo-controlled trial in 24 patients fulfilling the MRC criteria for chronic bronchitis, oral salbutamol 4 mg and slow-release aminophylline (Phyllocontin) 450 mg produced similar and significant (p less than 0.05) mean increases in forced expiratory volume in one second (FEV1). A significantly greater increase in mean FEV1 and forced vital capacity (FVC) was seen when both drugs were given although there was no statistical evidence of synergistic interaction. Salbutamol significantly increased the mean distance walked in 12 minutes (12MD) (p less than 0.02) by 56 metres and a similar increase of 54 metres (p less than 0.001) was seen after Phyllocontin. With both drugs in combination mean 12MD increased by 51 metres (p less than 0.02 cf placebo), a change not significantly different from that observed with either drug alone. Oral salbutamol and Phyllocontin improve exercise tolerance in chronic bronchitis. The significantly greater changes in FEV1 and FVC resulting from simultaneous administration of the two drugs are not associated with further improvement in exercise tolerance.